ICT application in students from Physical Activity and Sports Science: WebCT virtual platform - Castillo-Rodríguez, Alfonso; Álvarez-Kurogi, Leandro (Historia y Comunicación Social, 2014)
Educational systems have been modified according to the evolution of modern society. In this study, blended learning (combining face-to-face and online learning) has been used for 2 academic years with students of the subject Structure and Organization of Sports Institutions, belonging to the degree of Sports Science, by means of the virtual platform called WebCT. The results indicate that students have had only 5% of incidents with this new teaching model, which leads us to conclude that this model of education is beneficial for students.
Keywords: Virtual teaching-learning; WebCT; pedagogical virtual platforms; Sport Sciences.